2009
DOI: 10.1111/j.1582-4934.2008.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of connective tissue growth factor in renal cells by histone deacetylase inhibitors

Abstract: Introduction Post-translational modifications of histone proteins affect chromatin organization, among them acetylation and deacetylation of the N-terminal tails of the core histones by histone acetyltransferases (HATs) and histone deacetylases (HDACs) [1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…We showed that expression levels of HDAC2, α‐SMA and TGF‐β1 are increased in nasal polyp tissues, which suggested that HDAC2 regulates myofibroblast differentiation and plays a role in nasal polyp formation. Several recent studies have suggested that TSA, an HDAC inhibitor, suppresses myofibroblast differentiation in hepatic stellate cells , skin fibroblasts , kidney cells , lung fibroblasts and corneal fibroblasts . In this study, we demonstrated that TSA inhibits TGF‐β1‐induced morphological changes, myofibroblast differentiation and ECM accumulation in NPDFs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We showed that expression levels of HDAC2, α‐SMA and TGF‐β1 are increased in nasal polyp tissues, which suggested that HDAC2 regulates myofibroblast differentiation and plays a role in nasal polyp formation. Several recent studies have suggested that TSA, an HDAC inhibitor, suppresses myofibroblast differentiation in hepatic stellate cells , skin fibroblasts , kidney cells , lung fibroblasts and corneal fibroblasts . In this study, we demonstrated that TSA inhibits TGF‐β1‐induced morphological changes, myofibroblast differentiation and ECM accumulation in NPDFs.…”
Section: Discussionsupporting
confidence: 64%
“…According to recent findings, trichostatin A (TSA), an inhibitor of HDACs, abrogates TGF‐β1‐induced ECM expression in renal , skin , cornea , liver and lung fibrosis tissues. However, the effects of TSA inhibition on myofibroblast differentiation in nasal polyposis have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CTGF in renal endothelial and epithelial cells can be influenced by HDAC inhibitors [141-143]. Interestingly, the expression of CTGF was differentially regulated by different HDAC inhibitors.…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, the expression of CTGF was differentially regulated by different HDAC inhibitors. CTGF was clearly up-regulated when endothelial cells were incubated with TSA, sodium butyrate and SAHA, nevertheless VPA was found to be less effective [141]; while in epithelial cells, CTGF expression was dependent on culture confluency and donor variability [142,143]. …”
Section: Reviewmentioning
confidence: 99%
“…In our own studies, we observed cell type dependent regulation of CTGF by HDAC inhibitors. CTGF was strongly upregulated in several types of endothelial cells, while in renal epithelial cell lines CTGF gene expression was reduced or remained unaltered upon treatment with HDAC inhibitors [109]. These data indicate that, in addition to the acetylation status of the histones, CTGF expression will be determined by cell type‐specific transcription factors, which are direct or indirect targets of HDACs.…”
Section: Epigenetic Regulation Of Ctgf—more Than An Epiphenomenon?mentioning
confidence: 99%